Lilin Aromaterapi - M. Ibrahim Baihaqi; Alif Finno Fidzaky; Ayunda Febri Kinanti; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Aromatherapy candles made from used cooking oil represent an eco-friendly and economically valuable entrepreneurial innovation. This proposal presents the utilization of used frying oil as a base material in producing aromatherapy candles, aiming to support the circular economy concept and provide an alternative solution to environmental pollution. The product formulation combines paraffin, beeswax, and natural essential oils, offering relaxation and comfort while also opening up new business opportunities. SWOT analysis and marketing strategies based on the 4Ps (Product, Price, Place, Promotion) serve as the foundation for business development. The results of the study show that aromatherapy candle businesses have strong potential to attract consumer interest, especially among young people, and can deliver significant social, economic, and environmental impact.